Effectiveness of tests to detect the presence of SARS-CoV-2 virus, and antibodies to SARS-CoV-2, to inform COVID-19 diagnosis: a rapid systematic review. Issue 1 (1st October 2020) - Jarrom, David; Elston, Lauren; Washington, Jennifer; Prettyjohns, Matthew; Cann, Kimberley; Myles, Susan; Groves, Peter
Abstract : Objectives: We undertook a rapid systematic review with the aim of identifying evidence that could be used to answer the following research questions: (1) What is the clinical effectiveness of tests that detect the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to inform COVID-19 diagnosis? (2) What is the clinical effectiveness of tests that detect the presence of antibodies to the SARS-CoV-2 virus to inform COVID-19 diagnosis? Design and setting: Systematic review and meta-analysis of studies of diagnostic test accuracy. We systematically searched for all published evidence on the effectiveness of tests for the presence of SARS-CoV-2 virus, or antibodies to SARS-CoV-2, up to 4 May 2020, and assessed relevant studies for risks of bias using the QUADAS-2 framework. Main outcome measures: Measures of diagnostic accuracy (sensitivity, specificity, positive/negative predictive value) were the main outcomes of interest. We also included studies that reported influence of testing on subsequent patient management, and that reported virus/antibody detection rates where these facilitated comparisons of testing in different settings, different populations or using different sampling methods. Results: 38 studies on SARS-CoV-2 virus testing and 25 studies on SARS-CoV-2 antibody testing were identified. We identified high or unclear risks of bias in the majority of studies, most commonly as a result of unclear methods of patient selection and test conduct, or because of the use of a reference standard that may not definitively diagnose COVID-19. The majority were in hospital settings, in patients with confirmed or suspected COVID-19 infection. Pooled analysis of 16 studies (3818 patients) estimated a sensitivity of 87.8% (95% CI 81.5% to 92.2%) for an initial reverse-transcriptase PCR test. For antibody tests, 10 studies reported diagnostic accuracy outcomes: sensitivity ranged from 18.4% to 96.1% and specificity 88.9% to 100%. However, the lack of a true reference standard for SARS-CoV-2 diagnosis makes it challenging to assess the true diagnostic accuracy of these tests. Eighteen studies reporting different sampling methods suggest that for virus tests, the type of sample obtained/type of tissue sampled could influence test accuracy. Finally, we searched for, but did not identify, any evidence on how any test influences subsequent patient management. Conclusions: Evidence is rapidly emerging on the effectiveness of tests for COVID-19 diagnosis and management, but important uncertainties about their effectiveness and most appropriate application remain. Estimates of diagnostic accuracy should be interpreted bearing in mind the absence of a definitive reference standard to diagnose or rule out COVID-19 infection. More evidence is needed about the effectiveness of testing outside of hospital settings and in mild or asymptomatic cases. Implementation of public health strategies centred on COVID-19 testing provides opportunities to explore these important areas of research.